Investigating Figurative Language Use in the Selected Songs of “Wicked: For Good” Musical Fantasy Film - Srimaharani Tanjung; Abdurrohman Septiadi (Universitas Islam Negeri Palopo, 2025)
The aim of this research is to interpret the figurative language in the lyrics of the songs that accompany the movie “Wicked: For Good”. The data consisted of the lyrics to all the songs (6 songs) in the soundtrack of “Wicked: For Good”. This research utilized a combination of descriptive qualitative method and content analysis design in order to demonstrate the types of figurative language and their meanings used in soundtracks. The soundtracks of the movies contained ascribed nine different types of figurative language comprising of personification, simile, metaphor, hyperbole, symbolism, irony, paradox, alliteration and repetition. Personification has five data points (10%), metaphor has twelve data points (24%), hyperbole has six data points (12%), irony has nine data points (18%), symbolism has five data points (10%), paradox has two data points (4%), alliteration has two data points (4%), and repetition has four data points (8%). The song lyrics from the soundtrack of the movie